ANALISIS KENAIKAN HARGA KEBUTUHAN POKOK MENJELANG BULAN RAMADHAN DI PASAR INDUK KAJEN - Shafiyya Zahra (Sahmiyya, 2023)
The increase in the price of basic necessities ahead of Ramadan and Eid al-Fitr is no longer a new thing in Indonesia. Therefore, the purpose of this study is to describe the basic needs that experience price increases, the factors that cause price increases in basic needs, and strategies to stabilise the price of basic needs before Ramadan. This research method uses a qualitative approach. Data sources in this study used primary data sources and secondary data. The data analysis techniques used are interview, observation and documentation analysis techniques. The results of this study concluded that at this time all types of chilli experienced price increases. Factors causing price increases include the large demand for basic needs but the lack of availability of these basic needs, raw material factors, production process factors, distribution factors, and government policy factors, the impact of the Russian and Ukrainian wars. The government's efforts to stabilise the price of basic necessities include implementing appropriate fiscal policies in the form of subsidies, fiscal incentives including tax and duty relief and budget optimisation. In addition to fiscal policy, the programmes implemented by the government to maintain price stabilisation in order to meet the needs of the community, especially those living below poverty standards, one of which is by conducting Pure Market Operations (OPM). Market Operation is an activity to avoid an increase in the price of an item, which is carried out by injection, to increase supply through private traders, BUMN, or directly to retail traders by setting prices at prices below the market price. To increase supply, the Government implements an import policy.